A Randomized Evaluation of a Demand Creation Lottery for Voluntary Medical Male Circumcision Among Adults in Tanzania. (1st October 2016) - Bazant, Eva; Mahler, Hally; Machaku, Michael; Lemwayi, Ruth; Kulindwa, Yusuph; Gisenge Lija, Jackson; Mpora, Baraka; Ochola, Denice; Sarkar, Supriya; Williams, Emma; Plotkin, Marya; Juma, James
Abstract : Background: Uptake of voluntary medical male circumcision (VMMC) among adult men has fallen short of targets in Tanzania. We evaluated a smartphone raffle intervention designed to increase VMMC uptake in three regions. Methods: Among 7 matched pairs of health facilities, 1 in each pair was randomly assigned to the intervention, consisting of a weekly smartphone raffle for clients returning for follow-up and monthly raffle for peer promoters and providers. VMMC records of clients aged 20 and older were analyzed over three months, with the number performed compared with the same months in the previous year. In multivariable models, the intervention's effect on number of VMMCs was adjusted for client factors and clustering. Focus groups with clients and peer promoters explored preferences for VMMC incentives. Results: VMMCs increased 47% and 8% in the intervention and control groups, respectively; however, the changes were not significantly different from one another. In the Iringa region subanalysis, VMMCs in the intervention group increased 336% (exponentiated coefficient of 3.36, 95% CI: 1.14 to 9.90; P = 0.028), after controlling for facility pair, percentage of clients ≥ age 30, and percentage testing HIV positive; the control group had a more modest 63% increase (exponentiated coefficient 1.63, 95% CI: 1.18 to 2.26; P = 0.003). The changes were not significantly different. Focus group respondents expressed mixed opinions about smartphone raffles; some favored smaller cash incentive or transportation reimbursement. Implications: A smartphone raffle might increase VMMC uptake in some settings by helping late adopters move from intention to action; however, this study did not find strong evidence to support its implementation broadly.